Evaluasi dan Perbaikan Website Project Management Internship pada PT. Digtive Global Media menggunakan Metode Human-Centered Design (HCD) - Faris Wibowo Putro; Diah Priharsari; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Project management is an agenda or activity carried out as part of a plan to control human resources in a company or company. This is done in order to realize the goal within a predetermined time with certain resources. Website is a collection of components consisting of text, images, animated sounds, which are interesting information media and are very popular so that they can be used as a medium for sharing information. On the project management internship website that has been provided by PT. DIGTIVE is a website that is only used for internships working for companies. The author evaluates the project management internship website against the background of the importance of using the website in relation to monitoring or controlling human resources. Especially for internships that do tasks or work remotely or WFH. In the evaluation at PT. DIGTIVE the author will use the Human Centered Design (HCD) method. Then in evaluating the website the author also uses an additional method in the form of System Usability Scale (SUS). System Usability Scale (SUS). The solution design evaluation stage is almost the same as the initial design evaluation, namely measuring usability which includes three aspects of effectiveness, efficiency and user satisfaction. The respondents who participated in this assessment are the same respondents who participated in designing the initial design assessment. The researcher's observations showed that overall all the respondents successfully completed the task. This can be seen from the calculation of the percentage of effectiveness obtained by 100%. In the aspect of efficiency, the average time required for working on the task. Information related to the tasks assigned is the fastest at 3.26 seconds. This aspect of user satisfaction uses a System Usability Scale (SUS) questionnaire. The respondents involved in the design of this solution were still the same as at the time of the initial design, which used 10 respondents consisting of 3 stakeholders and 7 internship children from PT. DIGTIVE.